Sufisme dan Perubahan Sosial: Kaum Tarekat dan Dinamika Sosial Keagamaan - Khamim, M. (UIN Raden Mas Said Surakarta, 2021)
Social change is a necessity. Every shift that occurs in society will trigger change. Religion is basically independent, which theoretically can be involved in terms of mutual influence with socio-economic realities. As an independent unit, for its adherents, religion has a high probability of determining patterns of human behavior and the form of social structures. In this way, religious teachings have the possibility to encourage or even restrain the process of social change. The existence of Sufism and tarekat in social life has an important role in social processes, one of which is social change. Through a qualitative descriptive approach with a research library that refers to related sources, this paper provides important point that tarekat has a dual function, namely as a religious-spiritual moral movement that directs its followers to always be close to God, and as a social and political social movement that helps guide its followers to have social sensitivity and care about social conditions, through the practice of teachings or doctrines that have been taught by tarekat organization.